2022
DOI: 10.3390/foods11152239
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Apricots of Different Geographic Origin in Central and Southern Europe by Applying 87Sr/86Sr Analysis: Potential and Limitations

Abstract: Consumers prefer food commodities of certain origins over the same products of other provenances and are willing to pay higher prices for them. Thus, it is possible to increase profit simply by giving an incorrect geographic origin to a product. To effectively control the declared geographic origin of food, the product itself has to be investigated to discover whether it actually originates from the declared origin, or if it has been mislabeled. Conventionally, control of a geographic origin is conducted by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…However, as Spain and Iran are both large countries, each possessing a very diverse and heterogenous geology, it needs to be verified if all saffron produced in these countries stems from areas with carbonate bedrock. Still, the 87 Sr/ 86 Sr value reported for Spanish apricots was also within the range observed for the Spanish saffron [40]. No differentiation between the Spanish and the Iranian samples or the Kashmiri and Moroccan saffron was possible judging solely by 87 Sr/ 86 Sr.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, as Spain and Iran are both large countries, each possessing a very diverse and heterogenous geology, it needs to be verified if all saffron produced in these countries stems from areas with carbonate bedrock. Still, the 87 Sr/ 86 Sr value reported for Spanish apricots was also within the range observed for the Spanish saffron [40]. No differentiation between the Spanish and the Iranian samples or the Kashmiri and Moroccan saffron was possible judging solely by 87 Sr/ 86 Sr.…”
Section: Discussionsupporting
confidence: 67%
“…However, some investigations have demonstrated the limitations (e.g., because of geological heterogeneities, difference in the 87 Sr/ 86 Sr of bedrock and covering sediment, changing of the natural 87 Sr/ 86 Sr owing to anthropogenic activities, etc.) of this method (e.g., [28,33,[37][38][39]), and Horacek et al (2022) [40] concluded that the value and power of this approach depends on the exact question that needs to be answered and the respective geological setting.…”
Section: Introductionmentioning
confidence: 99%
“…Tchaikovsky et al, 2019 [ 16 ], and Epova et al, 2019 [ 17 ], noted differences in salt 87 Sr/ 86 Sr ratios; however, neither work gives a detailed description of all locations of the origin of the salt, as other commodities (caviar and ham) were the foci of these studies. Still, the 87 Sr/ 86 Sr ratio of salt is another interesting and potentially relevant proxy to differentiate food and salt origin (also see Horacek et al, 2022 [ 18 ], and Horacek, 2022 [ 19 ]); however, it was not applied in the present study.…”
Section: Introductionmentioning
confidence: 97%
“…This method can be powerful, and has been demonstrated to potentially be very successful [ 21 , 22 , 23 , 24 ]. An added advantage is that annual collection and analysis of reference samples would no longer be necessary; however, limitations have been documented [ 25 , 26 , 27 , 28 ]. The data suggest that heterogeneous bedrock geology in areas where the geographic origin should be controlled might limit the relevance of the Sr-system concerning the control of geographic origin to specific cases and questions.…”
Section: Introductionmentioning
confidence: 99%
“…Other proposed methods for the control and differentiation of geographic origin are based on the additional measurement of element concentrations in wine [ 23 , 29 , 30 , 31 ]. However, there exists no general agreement about the main factors influencing the elemental patterns, as Leder et al, 2021 [ 30 ], relate these patterns mainly to enological practices, while Griboff et al, 2021 [ 31 ], (and other researchers, e.g., [ 32 ]) identify the geographic origin (bedrock) as a dominant factor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%